Discovery of tillite on the western flank of the Hedionda Water anticline (Province of San Juan): evidence of ice movement during the Gondwana glaciation in the Paganzo River Basin - Marenssi, S.A. (2002)
Fil:Marenssi, S.A. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.